2019
DOI: 10.3389/fenvs.2019.00147
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Importance of Polyphenols for Microbial Carbon Mineralization in Rewetted Riparian Peatlands

Abstract: There have been widespread attempts to rewet peatlands in Europe and elsewhere in the world to restore their unique biodiversity as well as their important function as nutrient and carbon sinks. However, changes in hydrological regime and therefore oxygen availability likely alter the abundance of enzyme-inhibiting polyphenolic compounds, which have been suggested as a "latch" preventing large amounts of carbon from being released into the atmosphere by microbial mineralization. In recent years, a variety of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

5
5

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 65 publications
0
29
0
Order By: Relevance
“…Microbiology: The microbiomes of peat soils are composed of bacteria, archaea and microbial eukaryotes and are important agents of carbon, nitrogen (N) and phosphorus (P) cycling. The phylogenetic composition and expression of catalyzing enzymes play a major role in peat formation and GHG emission [43,44]. Methane (CH 4 ), for example, is almost exclusively produced by methanogenic archaea as an end product of anaerobic respiration [45,46].…”
Section: Interacting Research Areas In the Wetscapes Approachmentioning
confidence: 99%
“…Microbiology: The microbiomes of peat soils are composed of bacteria, archaea and microbial eukaryotes and are important agents of carbon, nitrogen (N) and phosphorus (P) cycling. The phylogenetic composition and expression of catalyzing enzymes play a major role in peat formation and GHG emission [43,44]. Methane (CH 4 ), for example, is almost exclusively produced by methanogenic archaea as an end product of anaerobic respiration [45,46].…”
Section: Interacting Research Areas In the Wetscapes Approachmentioning
confidence: 99%
“…The complex microbiomes of peat soils are composed of bacteria, archaea and microbial eukaryotes and are important agents of C, N and P cycling. The phylogenetic composition and expression of catalyzing enzymes play a major role in peat formation and GHG emission [42,43]. Methane (CH4) for example is almost exclusively produced by methanogenic archaea as an end product of anaerobic respiration [44,45].…”
Section: The Wetscapes Approachmentioning
confidence: 99%
“…The enzymic latch theory implies that the increase in phenols, due to a decrease of phenoloxidase activity, inhibits the activity of hydrolytic enzymes, and thereby facilitates the accumulation of organic matter. In recent years, this theory has been widely discussed, with studies that have provided both positive and negative evidence [53,64]. Although the present research is focused on verifying this theory, the differences found seemed to provide evidence for the recovery of the "enzymic latch" in NWS with respect to CS.…”
Section: Discussionmentioning
confidence: 59%